Curvilinear Grid Frames - Hutton, Charles R. (Engineering Journal, 1964)
In dealing with a structural system for the first time, especially when the system is new, one finds himself consciously involved in many facets of design which would ordinarily be intuitive in the more familiar systems of construction. One must first satisfy himself about the limits and the possibilities of the systems per se, before he can even begin to think about developing an architecture out of the constructional method. The use of curved surfaces is a case in point. From a structural point of view, there are two problems which face a designer. The first deals with a succinct knowledge of the stress distribution within the framework of the design project, and the second with the assurance that the materials applied to the resolution of the internal stress pattern will react in a predictable manner. The first is usually a paper problem using a more or less idealized situation. The second is a laboratory or field problem. Not all structures are capable of a rational analysis, particularly shells, and those structures, if built, must undergo experimental analysis to a lesser or greater degree. This is where the applied researcher renders his valuable service. And yet his role also involvesthe examination of those units for which there is a rational approach, if for nothing else than to instill confidence in a particular analytical method.